Desired recreation companionship and travel behaviour of people with disabilities. Issue 4 (3rd April 2019) - Chung, Jin Young; Lee, Hoon
ABSTRACT: This study examines whether people with disabilities(PWD) participate in leisure and travel activities with their desired companions and if there are discrepancies between their social networks and real recreation companions. The recreation companionship and travel behaviour of PWD have not been thoroughly explored, particularly in non-Western contexts. Accordingly, data were collected from 494 respondents in South Korea, and findings suggest that there was a significant gap between companions PWD desire and those they actually maintain. Travel and tourism were the least frequent recreation activities for PWD. The results can provide managerial implications regarding practices of inclusive and accessible tourism.